EXAMINING SHARIA STOCK SCREENING STANDARDS AND THEIR IMPACT ON ECONOMIC STABILITY IN THE ASEAN ECONOMIC COMMUNITY - Deva Nabilah; Khadijatul Musanna; Benny Sultan; Shahzulhemi Aiman (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2025)
This study aims to analyze the standard of sharia stock screening process and its impact on economic stability in the context of the ASEAN Economic Community (AEC), reviewed from the perspective of Maqāṣid Asy-Syarīah. Sharia stock screening is the process of evaluating a company's shares to ensure compliance with sharia principles, which include financial, ethical, and operational aspects. In the context of the AEC, this standard plays an important role in maintaining economic stability, by ensuring that investments made are in accordance with Islamic values. This study uses a qualitative analysis method with a descriptive-analytical approach. The data used were obtained from secondary sources such as journals, books, and official reports. The results of the study indicate that strict sharia stock screening standards contribute to economic stability, by encouraging ethical and responsible investment. In addition, the implementation of this standard in the context of the AEC is also in line with the objectives of Maqāṣid Asy-Syarīah, especially in protecting the interests of the people, maintaining justice, and promoting shared prosperity. Therefore, this study suggests strengthening and harmonizing sharia stock screening standards at the ASEAN level to support broader economic stability and prosperity.